Endoscopic Ultrasound/Fine Needle Aspiration Is Effective for Lymph Node Staging in Patients With Cholangiocarcinoma. Issue 3 (9th July 2020) - Malikowski, Thomas; Levy, Michael J.; Gleeson, Ferga C.; Storm, Andrew C.; Vargas, Eric J.; Topazian, Mark D.; Abu Dayyeh, Barham K.; Iyer, Prasad G.; Rajan, Elizabeth; Gores, Gregory J.; Roberts, Lewis R.; Chandrasekhara, Vinay
Abstract : Background and Aims: Presence of malignant regional lymph nodes (MRLNs) precludes curative oncological resection or liver transplantation for cholangiocarcinoma (CCA). Limited data support the utility of endoscopic ultrasound (EUS)/fine needle aspiration (FNA) for detection of MRLNs in extrahepatic CCA, but there are no data for its role in intrahepatic CCA (iCCA). The aim of this study is to evaluate the staging impact of EUS for CCA, including analysis by subtype. Approach and Results: We identified consecutive patients with CCA who underwent EUS staging at a single tertiary care center from October 2014 to April 2018. Among this cohort, we abstracted clinical demographic, radiographical, procedural, cytopathological, and surgical data. STATA 15 software was used for comparative analysis calculations (StataCorp LP, College Station, TX). The study cohort included 157 patients; 24 (15%), 124 (79%), and 9 (6%) with intrahepatic, perihilar, and distal CCA, respectively. EUS was able to identify regional lymph nodes (RLNs) in a higher percentage of patients compared to cross‐sectional imaging (86% vs. 47%; P < 0.001). FNA was performed in 133 (98.5%) patients with RLNs, with a median of three passes per node. EUS‐FNA identified MRLN in 27 of 31 (87.1%) patients ultimately found to have MRLNs. For iCCA, EUS detected a higher percentage of RLN compared to cross‐sectional imaging (83% vs. 50%; P = 0.048), with MRLNs identified in 4 (17%) patients. Among the entire cohort, identification of at least one MRLN by EUS was associated with lower median survival (353 vs. 1, 050 days; P < 0.001) and increased risk of death (hazard ratio = 4.1; P < 0.001). Conclusions: EUS‐FNA is effective for identifying MRLN in patients with CCA, and should be routinely incorporated into staging of all CCA subtypes given the impact of MRLN on prognosis and management decisions.